IMPLEMENTATION OF ONLINE CULTURAL ARTS (DANCE) LEARNING VIA GOOGLE MEET AT SATAP ELEMENTARY SCHOOL - JUNIOR HIGH SCHOOLS 08 KABAENA BARAT SOUTHEAST SULAWESI - Selfiana Saenal; Sumiani HL (JURNAL PAKARENA, 2021)
The purpose of this study is to find out and describe the implementation of Cultural and Arts (dance) learning by using Google Meet at SD-SMP SATAP NEGERI KABAENA BARAT SOUTHEAST SULAWESI. This research is qualitative research using descriptive methods. Where the research instruments used are the researchers themselves and are supported by additional instruments such as laptops, mobile phones, cameras, and stationery. The types of data used in this study are primary data and secondary data. Data collection is done through literature studies, observations, and documentation. The steps in data analysis are reducing data, presenting data, and drawing conclusions. The results showed that the implementation of online art learning (dance) reviewed from the level of material and dance patterns in elementary-junior high school using Google Meet went very well, although not yet maximally. Judging from the planning, the learning design carried out by teachers remains the same but the implementation steps are different because the learning system uses the Google Meet application. Teachers are more flexible in using learning media. Teachers who used to only use textbook media, now the media used is more interesting with the use of video, both videos that are shown live or videos that are played and sent through the Google Meet share screen feature. In terms of assessment is done by looking at the assignments given by students and quiz scores. In terms of the implementation of knowledge learning materials, it is carried out very well. This is evident from the results of assignments given by students. No students have their grades below. Although the delivery of student assignments is often not on time because of internet network problems, the results of the tasks submitted are quite good. In addition, students can create in terms of floor patterns. This proves that students can look for additional materials other than those provided by the teacher.